Alterações endócrinas, de densidade mineral óssea, autoimunidade e seu impacto na qualidade de vida de pacientes com sobrecarga de ferro - Lima, Tadeu Gonçalves de (2019)
Endocrine, bone mineral density, autoimmunity and its impact on the quality of life of patients with iron overload Introduction: Iron is an essential element of normal metabolism, but its potential for damage in overload situations results in impairment of the function of various tissues. Objectives: To evaluate endocrine dysfunction, changes in bone mineral density (BMD) and presence of autoantibodies and their impact on quality of life in patients with iron overload. Patients and methods: An observational, cross-sectional study was performed at HUWC/Hemoce between August/2017 and June/2018, in iron overload patients. We evaluated epidemiological and clinical aspects with a specific form and aspects of quality of life with WHOQoL-Bref. Laboratory tests and review of medical records were used to evaluate gonadal and thyroid function, glycemic and bone metabolism, autoimmunity and iron deposits. Ultrasonography (USG) was used to evaluate structural thyroid changes and bone densitometry to assess BMD. Results: Twenty-five patients, mean age 50.9 ± 3.4 years, were included in the study; 09 had hereditary hemochromatosis (HH) and 16 had secondary hemosiderosis (SH). Sixteen (64%) were women, of whom 13 (81%) had HS. Among the 9 males, 6 (66.7%) had a diagnosis of HH. We identified some endocrinopathy in 14 (56%) patients, with no predominance between HH and SH. Diabetes mellitus was observed in 5 (20%) patients and glucose intolerance in 2 (8%), with no higher prevalence of obesity or overweight in this group. Eight (32%) were diagnosed with hypogonadism, where 7 (87.5%) had no previous diagnosis. Four (16%) presented changes in thyroid function, with 01 case of hyperthyroidism. The BMD was altered in 14, 8 with osteopenia and 6 with osteoporosis. Age, age at diagnosis and hypogonadism were related to altered BMD. The prevalence of anti-thyroglobulin and anti-thyroperoxidase (anti-TPO) was 44% and 12%, respectively. Thyroid dysfunction was associated with changes in volume (p <0.0001), echotexture (p = 0.003), contours (p = 0.04) and echogenicity (p <0.0005) and presence of anti-TPO with volume (p = 0.029) and echogenicity (p = 0.034) changes in USG. The group with endocrine alterations presented a high frequency of low levels of quality of life. Conclusion: We observed high prevalence of endocrine changes and BMD in iron overload patients. Hypogonadism was the most underdiagnosed endocrinopathy and is associated with BMD changes. We also demonstrate the impact of these diseases on quality of life.